An Analysis of Politeness Strategies in Makna Talks Podcast Episode "Living Life to the Fullest" - Evi Zainuri Putry; Salsabila - Putri; Afiifah Al Rosyiidah (Journal of Social, Culture, and Language, 2026)
This study analyses the types of politeness strategies used in the Makna Talks podcast entitled “Living Life to the Fullest” with Nicholas Saputra, based on Brown and Levinson’s (1987) theory of politeness. Using a descriptive qualitative method, the writers analyzed the transcript of the episode and identified utterances that demonstrated politeness strategies. The writers found 75 data points and categorized them into four types of politeness strategies. The results showed that positive politeness was used most frequently (45 data points), followed by the bald on record strategy (18 data points), negative politeness (9 data points), and the off record strategy (6 data points). Positive politeness demonstrated the friendliness between the host and guest. The bald on record strategy demonstrated spontaneity and provided clarity. Negative politeness arises in situations that require caution, while the off-record strategy emerges when the speaker uses indirect messages. Thus, this study emphasises the use of politeness strategies to maintain facial expressions, appropriate language use, and create good relationships so that digital conversations such as podcasts are comfortable and relaxed. Keywords: politeness strategies, Brown Levinson, Pragmatics, Makna Talks, podcast conversations